THE EFFECT OF THE WORK ENVIRONMENT ON EMPLOYEE MORALE IN THE MEDAN CITY POPULATION AND CIVIL REGISTRY OFFICE - Oktaviani, Anggi; Sihombing, Tunggul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The quality public services can be fulfilled when the agency is able to manage the morale of each employee well. High morale will encourage employees to work optimally. However, classical issues related to public services are in fact still often occur at Medan City Population and Civil Registration Agency where the administration process provided is still considered complicated and slow by the society. This study aims to determine and analyze the influence of the work environment on employee morale. The type of research used is associative (relationship) with a quantitative approach. The sampling of 55 public civil servants at Medan City Population and Civil Registration Agency was carried out using probability sampling technique. Data obtained through questionnaires were analyzed descriptively and processed using SmartPLS program. The results of this study indicate that: 1) the work environment condition is at 4.08 which means entering in good category, 2) the employee morale earned a 4.20 so it is classified in a high-level, 3) the work environment has a positive and significant effect on employee morale with R Square value of 0,577. This means that the contribution of the work environment influence to the morale of employees at Medan City Population and Civil Registration Agency are at 57,7% and other 42,3% is influenced by other variables beyond this study.